ANALISIS TINGKAT PENGETAHUAN DAN PENERAPAN ILMU KESEHATAN DASAR PADA PESERTA DIDIK DI SD INPRES MOEPALI - Boy Ardian Gerimu; Yessy Mata (CV. ADIBA ASIHA AMIRA, 2026)
Basic health is a crucial factor in supporting the learning process of elementary school students. Children of this age have developing immune systems, making them susceptible to various illnesses. This study aims to assess the level of knowledge regarding basic health among students at SD Inpres Moepali. A descriptive research method was employed, utilizing observation and documentation. The results indicate that the majority of students practice healthy living habits; however, continuous guidance is still required. To ensure the effective implementation of health education and foster clean and healthy living behaviors among students, the active involvement of both teachers and parents in providing regular basic health education is essential.